1994
DOI: 10.1111/j.1348-0421.1994.tb01831.x
|View full text |Cite
|
Sign up to set email alerts
|

A Sandwich Cup Method for the Penetration Assay of Antimicrobial Agents through Pseudomonas Exopolysaccharides

Abstract: We developed new sandwich cup method to assay the penetration of various antimicrobial agents through Pseudomonas exopolysaccharides. Using alginate extracted from mucoid‐type Pseudomonas aeruginosa and gellan gum from Pseudomonas elodea, the role of exopolysaccharides as a barrier against drug penetration was examined. The penetration of positively charged hydrophilic drugs such as aminoglycosides and polypeptides was markedly inhibited by the gels tested, but that of β‐lactams, quinolones, and macrolides was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 16 publications
5
73
2
2
Order By: Relevance
“…Our data show that LVX and GAT have signifi cant inhibitory effect against both BLNAS and BLNAR NTHi within biofi lms compared to AMP, CTX, ERY and CLR. Our results agree with previous investigations that studied P. aeruginosa biofi lm, as it has been shown that fl uoroquinolones can penetrate exopolysaccharides (Kumon et al 1994;Yassien et al 1995). Since the use of fl uoroquinolones in young children is limited in many countries because of adverse neurological side effects, the clinical antimicrobial effectiveness against BLNAS and BLNAR NTHi in biofi lms has not been confi rmed.…”
Section: Discussionsupporting
confidence: 79%
“…Our data show that LVX and GAT have signifi cant inhibitory effect against both BLNAS and BLNAR NTHi within biofi lms compared to AMP, CTX, ERY and CLR. Our results agree with previous investigations that studied P. aeruginosa biofi lm, as it has been shown that fl uoroquinolones can penetrate exopolysaccharides (Kumon et al 1994;Yassien et al 1995). Since the use of fl uoroquinolones in young children is limited in many countries because of adverse neurological side effects, the clinical antimicrobial effectiveness against BLNAS and BLNAR NTHi in biofi lms has not been confi rmed.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, the effect of an antibiotic can be reduced after adsorption on the matrix due to electrical interactions with polymers surrounding biofilm bacteria (20,36). Other studies reported slow penetration of positively charged aminoglycosides through negatively charged polymers of the biofilm matrix (37,38). In this regard, the chemical structure of the biofilm matrix is important, and it has been shown that even for a single pathogen, different types of exopolysaccharides can be involved, depending on the environment surrounding the biofilm (39).…”
Section: Biofilm Recalcitrance Is Multifactorialmentioning
confidence: 99%
“…Biofilm structure can prevent an applied antimicrobial agent from reaching the entire bacterial population by mechanisms such as a neutralizing reaction with components of the biofilm [29,10], synthesis of an antimicrobial degrading enzyme [16,3] and adsorption of the antimicrobial by the exo-polymeric substance (EPS) [19]. There have been several mathematical models of biofilm disinfection that include diffusion and various antimicrobialdegrading reactions [25,12,6].…”
Section: Introductionmentioning
confidence: 99%